2019
DOI: 10.1634/theoncologist.2019-0292
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide, Multicenter Registry Study of Antiemesis for Carboplatin-Based Chemotherapy-Induced Nausea and Vomiting in Japan

Abstract: Background. We previously reported the results of a prospective study of chemotherapy-induced nausea and vomiting (CINV) in a cohort of patients who received carboplatin-based chemotherapy and were selected from a nationwide registry of those scheduled for moderately (MEC) or highly emetogenic chemotherapy (HEC) by the CINV Study Group of Japan. Of 1,910 previously registered patients (HEC: 1,195; MEC: 715), 400 patients received carboplatin-based chemotherapy. The frequency of CINV was determined, and the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…Thus, 5 mg of OLZ might be more effective than adding NK 1 RA because of a high CR rate of 94.0%. We also found that the highest incidence of nausea and vomiting was on days 3–4, consistent with a previous report of two‐ or three‐drug combinations for CBDCA [34]. Therefore, it is necessary to closely monitor the onset of nausea and vomiting on days 3–4, despite administration of OLZ.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, 5 mg of OLZ might be more effective than adding NK 1 RA because of a high CR rate of 94.0%. We also found that the highest incidence of nausea and vomiting was on days 3–4, consistent with a previous report of two‐ or three‐drug combinations for CBDCA [34]. Therefore, it is necessary to closely monitor the onset of nausea and vomiting on days 3–4, despite administration of OLZ.…”
Section: Discussionsupporting
confidence: 90%
“…The hypothesis of this study was that the TC rate of 5 mg OZL in triplet group would be signi cantly higher than that of standard group. Other trials have shown that the TC rate of standard antiemetic therapy was about 40% [13] .We believed that an improvement of more than 15% in the TC rate would be clinically meaningful. Therefore, assuming that the null hypothesis of the TC rate is 55% and the alternative hypothesis is 80%, we calculated that a minimum of 90 patients were required to achieve a one-sided type I error of 0.1% and 80% of power, based on the exact binomial distribution.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, only 13.6% of patients prescribed HEC and 35.7% of patients prescribed MEC complied the NCCN 2019 guidelines, respectively, which were comparable with the results reported in the conducted by Aapro et al (11%, 39%, respectively). However, this was not a satisfactory result when compared with the GCCP prevalence in a Japanese study, in which Hirotoshi et al reported 96% of patients receiving carboplatin-based chemotherapy (HEC and MEC were both included) were in compliance with the antiemesis guidelines based on JSCO 2010 guidelines [14]. Except the fact of using different guidelines, Japan enacted the rst cancer control law in 2006, which con rmed that political policies could in uence compliance with guidelines [14].…”
Section: Discussionmentioning
confidence: 95%